PENGARUH KOMITMEN ORGANISASI DAN KOMPENSASI TERHADAP KEPUASAN KERJA KARYAWAN PADA CV. LAKITAN PADANG (JURNAL ECONOMICA : Research of Economic And Economic Education, 2013)
This study aims to measure the effect of organizational commitment on job satisfaction and employee compensation. Data collection techniques using sampling that is numbered 35 total employees. Method of data collection is using questionnaires. Filling the questionnaire sought only takes 15 minutes so it was not so time-consuming respondents. The variables used in this study are the commitment of the organization and compensation as the independent variable, while the dependent variable is employee satisfaction. The method of analysis used is multiple linear regression method was used to determine whether or not the influence of the independent variables with the dependent variable. Organizational Commitment variable has a positive effect (ß = 0.089) and significant (α = 0.019) on employee satisfaction. Compensation variable has a positive effect (ß = 0.078) and significant (α = 0.028) towards employee satisfaction.